Nested PCR Targeting the Flagellin Gene (fliC) in Urine Sample for Diagnosis of Typhoid Fever – An Internal Pilot Study - Fouad, Mona Mohammad; Fathy, Maha Muhammad; Fathi, Marwa Saad Mohammed; El-Folly, Runia Fouad; Khater, Walaa Shawky (QJM : An International Journal of Medicine, 2024)
Introduction Typhoid fever remains a significant public health challenge, especially in developing countries. Diagnostic complexities arise from the disease’s non-specific clinical manifestations that overlap with other febrile illnesses. Hence, reliable laboratory testing is crucial. Nested polymerase chain reaction (PCR) stands out for its diagnostic performance, especially when utilizing urine due to its minimal PCR inhibitors and ease of collection. Aim The study aimed to test the performance of Salmonella enterica serotype Typhi (Salmonella Typhi) fliC gene specific nested PCR in urine for laboratory diagnosis of typhoid fever. Subjects and Methods This observational, cross-sectional study was conducted as an internal pilot study during the period from August 2021 to October 2022. It included 25 clinically diagnosed enteric fever patients, recruited from Al-Abasseya Fever Hospital, Cairo, Egypt, and 25 healthy individuals as controls, matched for age and sex. Nested PCR was performed to detect the fliC gene of Salmonella Typhi in urine samples from both patients and controls. Urine culture was conducted for subjects in both groups, while blood and stool cultures were exclusively performed for the patients' group. Results The sensitivity of the nested PCR test targeting the fliC gene in urine was 44%, with a specificity of 88%. The positive predictive value was 78.57%, the negative predictive value was 61.11%, the positive likelihood ratio was 3.7, and the negative likelihood ratio was 0.63. Blood culture isolation exhibited a very low positivity rate of 4%. Conclusion Nested PCR targeting the fliC gene in urine samples holds promise as a diagnostic tool for typhoid fever. Despite its moderate sensitivity, the relatively higher specificity suggests its potential utility in confirming typhoid fever cases. The test offers a valuable adjunctive tool alongside conventional diagnostic method. However, further research and validation may be necessary before widespread clinical application. The performance of the test needs to be evaluated in clinically diagnosed and laboratory confirmed cases of typhoid fever.